Features of formation of communicative of future teachers of non-philological specialties (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article analyzes the views of native and foreign scientists on the nature of the concepts of «competence», «competency», «communicative competence» in modern linguodidactic dimension. It was found the characteristics and defining features of these concepts, proved the importance of formation of communicative competence of students of pedagogical universities.
Keywords: competency; competence; communicative competence; linguistic culture